2008
DOI: 10.1007/s11251-008-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of representational guidance during computer-supported collaborative learning

Abstract: This research investigates the role of representational guidance by comparing the effects of two different representational tools. We used a design with two different groups defined by the type of argumentative diagram students co-constructed while working in a computer-supported collaborative learning (CSCL) environment. The Graphical Debate-tool offered different representational guidance than the Textual Debatetool. The results show that groups that worked with the Graphical Debate-tool constructed represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 44 publications
5
42
0
Order By: Relevance
“…This result is in line with conclusive findings in research on CSCL showing various added values and benefits of collaboration with external representations (e.g. Ertl et al 2008;Fischer et al 2002;Janssen et al 2007Janssen et al , 2010Nussbaum et al 2007;Toth et al 2002;Van Amelsvoort et al 2007. In this study, students benefitted from their partners' knowledge (knowledge awareness) by looking at one another's individually made graphical knowledge maps in CSCL environments.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result is in line with conclusive findings in research on CSCL showing various added values and benefits of collaboration with external representations (e.g. Ertl et al 2008;Fischer et al 2002;Janssen et al 2007Janssen et al , 2010Nussbaum et al 2007;Toth et al 2002;Van Amelsvoort et al 2007. In this study, students benefitted from their partners' knowledge (knowledge awareness) by looking at one another's individually made graphical knowledge maps in CSCL environments.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Extensive prior research has shown various benefits of external representations in the form of graphical knowledge maps (e.g. Ertl et al 2008;Janssen et al 2010;Toth et al 2002;Van Amelsvoort et al 2007). Various forms of graphical knowledge representation, such as argumentative texts, graphs, and diagrams, are useful for maintaining learners' focus on the relevant aspects of the task, which could broaden and deepen discussion and therefore improve learners' knowledge (Baker et al 2007;Suthers 2001;Noroozi et al 2011;Nussbaum 2008;Nussbaum et al 2007;Van Amelsvoort et al 2008;Veerman et al 2002).…”
Section: Cscl With Graphical Knowledge Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Stahl 2009a;Hmelo-Silver et al 2013) and empirical studies (e.g., Baker 1999;Barron 2003;Hmelo-Silver 2004;Mercer 2002) that have unfolded over the years have not addressed the details of learning in interaction that leads to knowledge production and challenges students to engage in sustained collaborative efforts. While some research studies on collaboration have provided substantial insight into whether and when interaction proves more effective than working alone (e.g., Furberg et al 2008;Janssen et al 2010), others have emphasized the role of different variables in mediated interaction (cf. Cress et al 2013;Slof et al 2013) or focused on the procedural characteristics of the process, such as social aspects, conflict, or planning (Barron 2003;Engle and Conant 2002;Remesal and Colomina 2013).…”
mentioning
confidence: 99%
“…It was shown that providing representational guidance can nudge the discussion of controversial evidence (Suthers, 2001) and can lead to learning outcomes of higher quality (Janssen et al, 2010). Recently, cognitive group awareness tools were proven to be beneficial for learning processes and learning outcomes in various CSCL and related scenarios (Bodemer and Dehler, 2011;Janssen and Bodemer, 2013).…”
Section: /25mentioning
confidence: 99%